Aerobic exercise improved liver steatosis by modulating miR-34a-mediated PPARα/SIRT1-AMPK signaling pathway - Baoai Wu; Zhibin Zhang; Chong Xu; Jinfeng Zhao (PLoS ONE, 2025)
MicroRNA-34a (miR-34a) was closely associated with liver steatosis. However, the link between changes in miR-34a and the progression of liver steatosis remained unclear. In the work, sixty mice were randomly and equally selected into six groups: normal control group (NC), normal exercise group (NE), high-fat diet group (HFD), high-fat diet plus exercise group (HFE), miR-34a overexpression group (OE), and miR-34a overexpression plus exercise group (OEE). Live morphology showed that treadmill exercise intervention for 8 weeks reduced high-fat diet-induced liver steatosis in mice. 8-week treadmill exercise directly decreased mir-34a expression of mice in HFD group, confirmed in OE group. More, treadmill exercise enhanced the expression of PPARα and SIRT1, thereby affecting the downstream hepatic steatosis-associated target genes, including CPT1(Carnitine palmitoyltransferase 1), CPT2(Carnitine palmitoyltransferase 2), SLC27A1(Solute carrier family 27 member 1), SLC27A4(Solute carrier family 27 member 4), in addition to activating the expression of the central metabolic sensor AMPK. Following aerobic exercise intervention, miR-34a was downregulated, thereby affecting the expression of genes associated with hepatic steatosis, and this mechanism was confirmed in miR-34a overexpression mice. This study contributed to our understanding of the pathogenesis of hepatic steatosis and may provide new therapeutic approaches.